2008
DOI: 10.1080/00045600701734612
|View full text |Cite
|
Sign up to set email alerts
|

Market-Led Pluralism: Rethinking Our Understanding of Racial/Ethnic Spatial Patterning in U.S. Cities

Abstract: Vast differences between the U.S. city of today and that of a quarter-century and half-century ago call for a rethinking of conventional frameworks that provide an explanation of clustering/segregation along racial/ethnic lines. Accordingly, we put forth a new framework, market-led pluralism, that better fits today's realities. Existing frameworks-assimilation, stratification, and resurgent ethnicity-miss a central element of today's racial/ethnic residential mosaic, the market makers. At the center are housin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 59 publications
3
37
0
4
Order By: Relevance
“…This hypothesis is contradicted by formal theory and by simulation results such as we have presented here. Of course, although our attention here is narrowly focused on preference effects, we do not gainsay the fact that other important social dynamics also are present in urban life and exert independent effects on segregation (25). At the same time, we must stress that acknowledging the relevance of other factors does not undermine the conclusions we offer regarding preference effects.…”
Section: Simulationsmentioning
confidence: 95%
“…This hypothesis is contradicted by formal theory and by simulation results such as we have presented here. Of course, although our attention here is narrowly focused on preference effects, we do not gainsay the fact that other important social dynamics also are present in urban life and exert independent effects on segregation (25). At the same time, we must stress that acknowledging the relevance of other factors does not undermine the conclusions we offer regarding preference effects.…”
Section: Simulationsmentioning
confidence: 95%
“…Stratifikační teorie přikládá význam zejména diskriminaci cizinců na trhu s bydlením, jež vede k segmentaci realitního trhu a stratifikaci čtvrtí ve městě podle dostupnosti cizincům [Brown, Chung 2008;Walton 2012]. V postsocialistické společnosti potvrzují nezanedbatelný význam antiimigračních postojů studie z Ruska [Gorodzeisky, Glikman, Maskileyson 2015], Maďarska [Bimbi 2011], Polska [Meuleman, Davidov, Billiet 2009] či Česka [Burjanek 2001].…”
Section: Teoretická Východiska: Migrace Cizinců Do Postsocialistickéhunclassified
“…We expect that many Asians and Latinos living in metropolitan areas where their group numbers are too small to make possible an ethnic concentration would prefer to reside in neighborhoods where Whites and their group were mixed somewhat evenly, if that option was available. What appears simply as non-ethnic and market-led pluralism in the very low ethnic percentages in mixed neighborhoods with above-average incomes may be more the result of the small ethnic-group numbers in a metropolitan area (Brown and Chung, 2008). In the long run, if American society evolves toward a reduced salience of race and ethnicity, then market-led pluralism may be the only appropriate interpretation of low-percentage ethnic concentrations; but right now, we question whether that is the case.…”
Section: Resultsmentioning
confidence: 99%
“…According to the most thorough nationwide study measuring discrimination of this type, discrimination persists but during the 1990s it diminished greatly, except for Latinos in the rental housing market (Ross and Turner, 2005). Intensive study of a medium-sized metropolitan area (Columbus, Ohio) also showed that discrimination occurred occasionally but was the exception rather than the rule (Brown and Chung, 2008).…”
Section: Discriminationmentioning
confidence: 99%